2021
DOI: 10.3390/ijerph18063271
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Healthcare Access in Japan during the First Wave of the COVID-19 Pandemic, up to June 2020

Abstract: We evaluated the impact of the new coronavirus disease (COVID-19) on healthcare access in Japan in terms of the number of outpatients and hospitalized patients as well as the length of hospital stays, during the first wave of the pandemic, up to June 2020. This observational study evaluated the monthly average number of outpatients per day at hospitals, the average number of hospitalized patients per day, and the average length of hospital stays per patient, from December 2010 to June 2020, using the hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 20 publications
0
22
0
Order By: Relevance
“…The daily visit rates for anxiety, depression, and schizophrenia spectrum were significantly reduced by approximately 29.8%, 14.8%, and 13.3%, respectively. In addition, a Japanese study found a decrease in the number of outpatients in psychiatric hospitals [ 41 ]. These results suggest that patients with pre-existing mental illness tend to be more reluctant to visit hospitals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The daily visit rates for anxiety, depression, and schizophrenia spectrum were significantly reduced by approximately 29.8%, 14.8%, and 13.3%, respectively. In addition, a Japanese study found a decrease in the number of outpatients in psychiatric hospitals [ 41 ]. These results suggest that patients with pre-existing mental illness tend to be more reluctant to visit hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…This shows that the spread of the virus may increase the risk of recurrence due to enhanced social distancing and the lack of adequate medical services due to the closure of some medical centers. A study from Japan showed that the length of hospitalization for mental health care increased during COVID-19 [ 41 ]. In addition, another study found that psychiatric inpatients increased by 21.4% among those over 65 years of age following the COVID-19 outbreak.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of COVID-19 on healthcare access was evaluated regarding patient visits. As a result, limited access showed the crucial function of long-term monitoring of vulnerable people and the urgent necessity of supporting medical facilities in the future [19].…”
Section: Abbreviationsmentioning
confidence: 99%
“…The coronavirus disease 2019 (COVID‐19) pandemic has spread worldwide, with many cases occurring in Japan. People are reluctant to visit healthcare facilities due to concerns regarding contracting COVID‐19 12 . According to a recent survey of 1000 men and women in their teens to their 70s conducted by the Japanese Association of Private Dental Schools, 13 21.4% of those surveyed reported that they discontinued regular dental visits during the period from February to August 2020, indicating that many individuals missed opportunities to receive professional dental care.…”
Section: Introductionmentioning
confidence: 99%